(untitled) (Journal of Fiber Bioengineering and Informatics, 2020)
The characteristics of a weft knitted fabric made of new cotton non-twisted hollow yarn targeting an inner wear product were investigated. The weight, thickness, thermal characteristics, tensile, shear properties, bending properties and surface properties of the knitted fabric and four commercially available inner wear fabrics were measured using a KES-FB system. The measured properties were examined to examine the usefulness of the new fabric for inner wear. Fabric characteristics were compared in a multiple comparison test. The knitted fabric made of non-twisted hollow yarn is lighter and fuller than commercially available inner wear fabrics. The shear stiffness and bending rigidities of the knitted fabric were similar or lower than ones of commercially available cotton inner wear fabrics. The surface properties of the new fabric were similar to ones of commercially available inner wear fabrics. The fabric also has a lower Q-max value (the peak value of heat transferred), lower thermal conductivity, and higher heat retention rate and is therefore warmer than the commercially available fabrics. It is thus considered that knitted fabric made of new cotton non-twisted hollow yarn is suitable for inner wear.